Perceptual-cognitive expertise of handball coaches in their young and middle adult years - Fischer, L.; Baker, J.; Rienhoff, R.; Strauß, B.; Tirp, J.; Büsch, D.; Schorer, J. (Journal of Sports Sciences, 2016)
There is little research investigating the maintenance of perceptual-cognitive expertise in general and even less comparing coaches of different ages. The aim of this study was to test for perceptual-cognitive differences between age groups, licence levels, and their interaction. This study investigated differences in skilled performance between young and middle-aged coaches of three different skill levels. Participants performed an accuracy-oriented pattern recall (mean distance in pixel) and a time-oriented flicker test (mean detection time in ms). There were some significant differences between age groups and between skill groups for both tests, but no interactions. For the pattern recall test, the effect sizes were larger for skill level differences, while for the flicker test effects were larger for ageing. These results suggest coaches are able to maintain accuracy skills better than reaction timed tasks. This is in line with findings on speeded performance in general populations, which show declines with age. Moreover, results also support findings on perceptual expertise in skills where accuracy was important.